Daily Inhaled Corticosteroids Treatment Abolishes Airway Hyperresponsiveness to Mannitol in Defence and Police Recruits - Lake, Clair D.; Wong, Keith K. H.; Perry, Clare P.; Koskela, Heikki O.; Brannan, John D. (Frontiers in Allergy, 2022)
Background Airway hyperresponsiveness (AHR) is a key pathophysiological feature of asthma and causes exercise-induced bronchoconstriction (EIB). Indirect bronchial provocation tests (BPTs) (e.g., exercise, mannitol) aid to diagnose asthma and identify EIB. Daily inhaled corticosteroids (ICS) can abolish AHR caused by indirect stimuli. Where strenuous physical exertion is integral to an occupation, identification of those at risk of EIB is important and documentation of inhibition of AHR with ICS is required before recruitment. Methods/Objectives A retrospective analysis was performed on 155 potential recruits with AHR to mannitol who underwent follow-up assessment after daily ICS treatment to determine the proportion that can abolish AHR using ICS and to determine any predictors of the persistence of AHR. Results Airway hyperresponsiveness was abolished in the majority (84%, n = 130) over the treatment period (mean ± SD 143 ± 72days), and it was defined as the provoking dose of mannitol to cause a 15% fall in FEV1 (cumulative inhaled dose of mannitol to cause 15% fall in FEV1, PD15) improved from (GeoMean) 183 to 521 mg. Compared with recruits in whom AHR was abolished with daily ICS (i.e., no 15% fall in FEV1 to the maximum cumulative dose of mannitol of 635 mg), in those where AHR remained (16%, n = 25), baseline AHR was more severe (PD15: 85 mg vs. 213 mg, P < 0.001), baseline FEV1% was lower (89 vs. 96%; 95%CI:2–12, P=0.004), and they had a longer follow-up duration (180 vs. 136 days; 13–74, P = 0.006). Baseline FEV1% (adjusted odds ratio 0.85; 95%CI:0.77–0.93), FEV1/FVC (0.78; 0.67–0.90), FEF25−75% (1.15; 1.06–1.25), and airway reactivity to mannitol (%Fall/cumulative dose of mannitol multiplied by 100) (1.07; 1.03–1.11) predicted AHR remaining after daily ICS. Conclusion Airway hyperresponsiveness to mannitol can be abolished after 20 weeks of daily treatment with ICS. Inhibition of AHR is likely due to attenuation of airway inflammation in response to ICS treatment. Increased airway reactivity and lower spirometry variables predicted the persistence of AHR. Thus, those with a slower response to daily ICS on AHR can potentially be identified at the commencement of monitoring ICS using inhaled mannitol.